Investigation of the prevalence and clinical implications of ERBB2 exon 16 skipping mutations in Chinese pan-cancer patients - Shang, Yanhong; Mo, Jianming; Huo, Ran; Li, Xiaofang; Fang, Guotao; Wei, Zichun; Gu, Guomin; Zhu, Xiaodan; Zhang, Chan; Liu, Chunling; Yan, Dong (Frontiers in Oncology, 2023)
Background Although rare, ERBB2 exon 16 skipping mutations (ERBB2ΔEx16) have been implicated in resistance to anti-HER2 and anti-EGFR targeted agents. Our study investigated the prevalence and clinical significance of ERBB2ΔEx16 in Chinese pan-cancer patients. Methods We retrospectively screened 40996 patients, spanning 19 cancer types, who had available genomic profiles acquired with DNA-based next-generation sequencing (NGS). We characterized the clinical and molecular features of the ERBB2ΔEx16-positive patients. Furthermore, we also analyzed a pan-cancer dataset from the Cancer Genome Atlas (TCGA; n=8705). Results A total of 22 patients were detected with ERBB2ΔEx16, resulting in an overall prevalence rate of 0.054% (22/40996). Of them, 16 patients had lung cancer (LC; 0.05%, 16/30890), five patients had gastric cancer (GC; 0.35%, 5/1448), and one patient had ovarian cancer (0.12%, 1/826). Among the 16 LC patients, ERBB2ΔEx16 was detected in four treatment-naïve EGFR/ALK-negative patients and 12 EGFR-positive patients after the onset of resistance to EGFR tyrosine kinase inhibitors (TKIs). The treatment-naïve patients harbored no LC-associated oncogenic drivers except ERBB2 amplification, suggesting a potential oncogenic role for ERBB2ΔEx16. Consistently, ERBB2ΔEx16+ patients from TCGA data also carried no known drivers despite various concurrent alterations. In the 12 EGFR TKI-resistant LC patients, relative variant frequencies for ERBB2ΔEx16 were lower than in untreated patients, suggesting ERBB2ΔEx16 as secondary alterations following TKI treatment and thereby implicating ERBB2ΔEx16 in mediating therapeutic resistance. Conclusions Our study identified an overall ERBB2ΔEx16 prevalence rate of 0.054% and provided insights into the clinical implications of ERBB2ΔEx16 in Chinese pan-cancer patients.